Remote Work and Data Protection: How do Organisations Secure Personal Data Protection Compliance from Home? - Ribeiro, Sofia (Bobcatsss, 2023)
In the Information Society, business processes tend to become increasingly digital and operate in the virtual world. With the recent pandemic, this transformation has become almost mandatory. With their workers performing their duties remotely, organisations feel the need to digitally adapt their processes. Among several aspects of concern in these transmutations, one stands out: data protection. How can data protection be controlled remotely? Workers take to their homes their work equipment, their documents and their information with them - full of personal data. With the entry into force of the GDPR, organisations have a duty to register the treatment of information containing personal data. This requires that information circuits be controlled, i.e., a mapping of business processes and the information contained and transmitted in them. A case study was carried out with focus on the activities of the Data Protection Group of a private Portuguese research and development company in order to discover how an organisation, where the main asset is information, controls and monitors data protection compliance.